2000
DOI: 10.1016/s0005-2736(00)00125-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine interaction with glycerophospholipid liposomes studied by magic angle spinning solid state 13C-NMR and differential scanning calorimetry

Abstract: Phosphatidylserine (PS) extracted from pig brain and synthetic dipalmitoylphosphatidylcholine (DPPC) and dimyristoylphosphatidylcholine (DMPC) were used to make DPPC/DMPC and DPPC/PS large unilamellar liposomes with a diameter of approximately 1 microm. Chlorpromazine-HCl (CPZ), an amphipathic cationic psychotropic drug of the phenothiazine group, is known to partition into lipid bilayer membranes of liposomes with partition coefficients depending on the acyl chain length and to alter the bilayer structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
5
39
1
Order By: Relevance
“…In micromolar concentration CPZ causes large increases in the mean molecular areas in monolayers of acidic phospholipids, whereas no such molecular area increase is found for the neutral glycerophospholipids in monolayers [16]. Similar findings by us [17], using magic angle spinning solid state 13 C NMR on bilayer samples with partial hydration (12 H 2 O per phospholipid), showed that CPZ had low or no interaction on the acyl packing of liposomes made of phospholipids without a net negative head group charge and with saturated acyl chains, such as palmitoyl (DPPC) and myristoyl (DMPC), while it caused a large (5-15 ppm) shift to higher ppm values of¨30% of the acyl chain carbon resonances in liposomes composed of pig brain PS (PBPS) and DPPC. PS is a major anionic phospholipid in mammalian cell membranes like peripheral and central nervous system myelin and PBPS was subjected to CPZ interaction studies as PBPS bilayer and in a mixture with DPPC as a DPPC (60 mol%)/PBPS (40 mol%) bilayer.…”
Section: Introductionsupporting
confidence: 87%
“…In micromolar concentration CPZ causes large increases in the mean molecular areas in monolayers of acidic phospholipids, whereas no such molecular area increase is found for the neutral glycerophospholipids in monolayers [16]. Similar findings by us [17], using magic angle spinning solid state 13 C NMR on bilayer samples with partial hydration (12 H 2 O per phospholipid), showed that CPZ had low or no interaction on the acyl packing of liposomes made of phospholipids without a net negative head group charge and with saturated acyl chains, such as palmitoyl (DPPC) and myristoyl (DMPC), while it caused a large (5-15 ppm) shift to higher ppm values of¨30% of the acyl chain carbon resonances in liposomes composed of pig brain PS (PBPS) and DPPC. PS is a major anionic phospholipid in mammalian cell membranes like peripheral and central nervous system myelin and PBPS was subjected to CPZ interaction studies as PBPS bilayer and in a mixture with DPPC as a DPPC (60 mol%)/PBPS (40 mol%) bilayer.…”
Section: Introductionsupporting
confidence: 87%
“…Electron microscopy revealed that SUV were unilamellar. Large unilamellar vesicles (LUV) (ϳ1 m diameter) were prepared by extrusion as described (32).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, using a fluorescence depolarization membrane probe, nortriptyline and protriptyline were observed to have similar disordering effects on lipid T m in mixed liposomes composed of DPPC and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), but no effect could be seen in pure DPPC liposomes at 100 µM drug. [65] The TCAs amitriptyline, nortriptyline, imipramine, and desipramine were shown by calorimetry to have similarly lowered dipalmitoyllecithin lipid T m at 1 : 1 drug : lipid molar ratios, but the extra methyl group on imipramine and amitriptyline caused a multiphase thermal profile. [66] In contrast, another fluorescence study found that amitriptyline and nortriptyline had a greater lipid disordering effect than imipramine and desipramine in 1,2-dimyristoylsn-glycero-3-phosphocholine (DMPC), DMPC/cholesterol, and synaptosomal membranes (including effects on ATPase activity), but there was no apparent difference between amitriptyline and nortriptyline.…”
Section: Membrane Disordering Effects Of Tcasmentioning
confidence: 99%